2019
DOI: 10.2217/lmt-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy in Early-Stage NSCLC: Historical Review, Contemporary Evidence and Future Implications

Abstract: Clinical use of stereotactic body radiation therapy (SBRT) has increased dramatically over the last 2 decades and is the current standard-of-care in cases of inoperable early stage non-small-cell lung cancer. While surgical resection remains the standard-of-care for operable patients, several ongoing clinical trials are investigating the role of SBRT in these operative candidates as well. Taking into consideration the expanding role and utility of SBRT, this paper will: review the historical basis of SBRT; exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
(91 reference statements)
2
16
0
Order By: Relevance
“…Likewise, this study found toxicity in the same proportions as previous reports: 31% clinically symptomatic RP [about 10-20% of patients in literature (range: 0-49% among published studies)] with most patients having asymptomatic Grade 1 pneumonitis (2,(15)(16)(17), 14% G1 chest wall pain [10-40% in literature (32)], 7% transient G ≤ 2 radiation dermatitis [12-38% in literature (33)], and 4% rib fractures [0-23% in literature (34)] without other toxicity. No significant predictive factor of chest wall pain, radiation dermatitis or rib fractures was found, probably due to meeting dose constraints (35).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Likewise, this study found toxicity in the same proportions as previous reports: 31% clinically symptomatic RP [about 10-20% of patients in literature (range: 0-49% among published studies)] with most patients having asymptomatic Grade 1 pneumonitis (2,(15)(16)(17), 14% G1 chest wall pain [10-40% in literature (32)], 7% transient G ≤ 2 radiation dermatitis [12-38% in literature (33)], and 4% rib fractures [0-23% in literature (34)] without other toxicity. No significant predictive factor of chest wall pain, radiation dermatitis or rib fractures was found, probably due to meeting dose constraints (35).…”
Section: Discussionsupporting
confidence: 90%
“…When we started to treat patients in 2012, guidelines were less clear and CTV creation was debated (26). In our study, LC and OS were respectively over 95% and about 60% at the three-year point, which is consistent with previously published studies (1)(2)(3)25). No significant predictive factor of LC was found, probably because only three local failures were observed and adequate BED 10 was prescribed to the tumor.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Stereotactic body radiotherapy (SBRT) is widely accepted as the standard treatment for early stage nonsmall cell lung cancers (NSCLC) in patients who are not operative candidates [1][2][3]. The applications of thoracic SBRT has expanded over time and it is now increasingly used for the ablative treatment of metastatic lesions, particularly in the settings of oligometastatic and oligoprogressive disease [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the COMET study, the contribution of SBRT to oligometastatic disease in different primary tumors, including NSCLC, was examined, ablative dose administration especially for metastasis in NSCLC provided progression-free survival and survival advantage. [49,50]…”
Section: Post-operative Radiotherapy In Non-small Cell Lung Cancer (Pmentioning
confidence: 99%